2016
DOI: 10.1002/hbm.23236
|View full text |Cite
|
Sign up to set email alerts
|

PreSMA stimulation changes task‐free functional connectivity in the fronto‐basal‐ganglia that correlates with response inhibition efficiency

Abstract: Previous work using transcranial magnetic stimulation (TMS) demonstrated that the right pre-supplementary motor area (preSMA), a node in the fronto-basal-ganglia network, is critical for response inhibition. However, TMS influences interconnected regions, raising the possibility of a link between the preSMA activity and the functional connectivity within the network. To understand this relationship, we applied single-pulse TMS to the right preSMA during functional magnetic resonance imaging when the subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 81 publications
2
40
0
Order By: Relevance
“…Amongst the various processes by which the pre-SMA is considered to exert top-down control [34][35][36][37], our results suggest a predominant role in reactive motor inhibition, without a significant contribution to conflict resolution (see next section for interpretation). Previous imaging evidence shows activation of the pre-SMA during performance of the go no-go [38,39], or stop signal tasks [3][4][5]7,9,21].…”
Section: Motor Inhibitionmentioning
confidence: 63%
See 1 more Smart Citation
“…Amongst the various processes by which the pre-SMA is considered to exert top-down control [34][35][36][37], our results suggest a predominant role in reactive motor inhibition, without a significant contribution to conflict resolution (see next section for interpretation). Previous imaging evidence shows activation of the pre-SMA during performance of the go no-go [38,39], or stop signal tasks [3][4][5]7,9,21].…”
Section: Motor Inhibitionmentioning
confidence: 63%
“…Previous imaging evidence shows activation of the pre-SMA during performance of the go no-go [38,39], or stop signal tasks [3][4][5]7,9,21]. Greater pre-SMA activation has been associated with: (i) faster SSRTs [6], and (ii) stronger effective connectivity with the right caudate [40] and right IFG [37], related to gray matter densities [41]. Our results showing that continuous cTBS of the pre-SMA improves/speeds up motor inhibition is consistent with previous findings [6].…”
Section: Motor Inhibitionmentioning
confidence: 97%
“…Early monkey tract tracing showed that likely homologues of these prefrontal areas connect to the STN (Inase et al, 1999) (Nambu et al, 1997) (also see Haynes and Haber, 2013). Several human studies using diffusion tensor imaging have also reported such connections, and some have shown that white matter variability in these connections relates to the speed of stopping (Aron et al, 2007; Coxon et al, 2012; Danielmeier et al, 2011; Forstmann et al, 2012; Rae et al, 2015a; Xu et al, 2016). These specific connections provide an anatomical basis for a putative ‘hyperdirect pathway’ by which the STN can be quickly activated (Nambu et al, 2002).…”
Section: The Brain’s Network For Global Motor Stoppingmentioning
confidence: 98%
“…In addition to the striatum, the right inferior frontal gyrus (IFG) has long been recognized as playing an important role in proactive inhibition (Aron, Fletcher, Bullmore, Sahakian, & Robbins, 2003;Rubia, Smith, Brammer, & Taylor, 2003;Vink, de Leeuw, et al, 2015;Vink, Kaldewaij, et al, 2015). An increase in functional connectivity between this area and the basal ganglia has been shown to increase response inhibition efficiency (Xu et al, 2016) and rIFG activity has been correlated with stopping speed (Whelan et al, 2012). In contrast, hypoactivation of the rIFG in patients with ADHD has been linked to impaired response inhibition (Morein-Zamir et al, 2014).…”
Section: Discussionmentioning
confidence: 99%